QOF - Institut Agama Islam Negeri Kediri (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Journal of Qur'anic Studies and Interpretation (Tafsir).
Keywords: Qurʼan : Criticism, interpretation, etc : Periodicals; Qurʼan : Study and teaching : Periodicals; Qurʼan; Education